2008
DOI: 10.3201/eid1408.080062
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Molecular Characterization of a Canine Norovirus

Abstract: We identifi ed a novel calicivirus in a pup with enteritis. The isolate was related genetically (90.1% aa identity in the capsid protein) to a lion norovirus strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
120
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 14 publications
3
120
0
5
Order By: Relevance
“…Human infection has been associated with genogroups I, II and IV while genogroups III and V infect cows and mice, respectively (Zheng et al 2006;Scipioni et al 2008;Clarke et al 2012). Porcine strains and a strain from lions are grouped in GII (Martella et al 2007) while a strain from a dog was identified in GIV (Martella et al 2008). Norovirus GII is detected more frequently than GI (Patel et al 2009;Vega et al 2013), though GI has been associated with outbreaks of waterborne gastroenteritis in Sweden (Nenonen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Human infection has been associated with genogroups I, II and IV while genogroups III and V infect cows and mice, respectively (Zheng et al 2006;Scipioni et al 2008;Clarke et al 2012). Porcine strains and a strain from lions are grouped in GII (Martella et al 2007) while a strain from a dog was identified in GIV (Martella et al 2008). Norovirus GII is detected more frequently than GI (Patel et al 2009;Vega et al 2013), though GI has been associated with outbreaks of waterborne gastroenteritis in Sweden (Nenonen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…GI and GII are further divided into many genotypes, and this classification is in constant evolution with the discovery of new strains. NoV has also been detected in several animal species, including swine, cattle, mice, lions, and dogs (21,28,30,32,51). Among them, bovine and murine strains are classified as GIII and GV, respectively, and are genetically distinct from human strains (21,37,42).…”
mentioning
confidence: 99%
“…However, for influenza virus, in addition to viral diversity generated from infections within the human population, new variants also emerge from zoonotic sources following reassortment events between human and avian and/or swine strains, such as with the emergence of the swine-origin H1N1 2009 pandemic strain (60). NoV strains have been identified in a wide range of animals, including pigs, cows, dogs, sheep, and mice (31,39,44,67,69). Furthermore, human NoVs have been shown to infect some nonhuman primates and pigs under experimental conditions (7,52,62).…”
mentioning
confidence: 99%